2014
DOI: 10.1039/c4sc00198b
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared light-responsive supramolecular nanovalve based on mesoporous silica-coated gold nanorods

Abstract: We constructed a novel cancer theranostic hybrid platform, based on mesoporous silica-coated gold nanorods (AuNR@MSN) gated by sulfonatocalix[4]arene (SC[4]A) switches, for bio-friendly near-infrared (NIR) light-triggered cargo release in a remote and stepwise fashion. The advantages of supramolecular switches, mesoporous silicas, and AuNRs were combined in one drug delivery system. Mesoporous silicas coated on AuNRs guarantee a high drug payload and can be easily post-functionalized.Significantly, the plasmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
111
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(117 citation statements)
references
References 45 publications
(69 reference statements)
6
111
0
Order By: Relevance
“…It was found that the stimulation of NIR light could obviously trigger drug release from WS 2 -IO@MS-PEG/DOX (Fig. 2b), similar to the behaviors of many other mesoporous silica coated photothermal nano-carriers [1,54,55]. Interestingly, the NIR light responsiveness of our nanocarrier was particularly sensitive within the acidic environment.…”
Section: Preparation and Characterization Of Ws 2 -Io@ms-peg/doxsupporting
confidence: 71%
“…It was found that the stimulation of NIR light could obviously trigger drug release from WS 2 -IO@MS-PEG/DOX (Fig. 2b), similar to the behaviors of many other mesoporous silica coated photothermal nano-carriers [1,54,55]. Interestingly, the NIR light responsiveness of our nanocarrier was particularly sensitive within the acidic environment.…”
Section: Preparation and Characterization Of Ws 2 -Io@ms-peg/doxsupporting
confidence: 71%
“…32 Various simple and robust methods have been reported for the synthesis of multifunctional mesoporous silica-encapsulated AuNPs (core-shell Au@mSiO 2 NPs) for use as cancer theranostics. 33,34 Previously, we successfully designed and synthesized Janus Au@mSiO 2 NPs, which might not only efficiently deliver imaging agents or drugs into cancer cells but also exhibit good photothermal properties, thus representing a promising theranostic candidate for use in combined photothermo-/chemo-cancer therapy. 30 Given …”
Section: Discussionmentioning
confidence: 99%
“…[40] The use of GNR allowed the authors to use near infrared light (NIR, 808 nm) to create heat around the nanodevice ( Figure 5). [40] The use of GNR allowed the authors to use near infrared light (NIR, 808 nm) to create heat around the nanodevice ( Figure 5).…”
Section: Plasmonic Heatingmentioning
confidence: 99%